Prevalence of Tuberculosis in Owerri West Local Government Area of Imo State (2008-2014) - Uneze , IjeomaMma; Uneze, IjeomaMma; Ezebuiro, Veronica O.; Okeke , Kalu Mgbo (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
The study determined the prevalence of tuberculosis in Owerri West local government area of Imo State. Three specific objectives were formulated with two research questions and two null hypotheses. Description research design was adopted for the study. The population for study consisted of 58 cases of TB in Owerri West from 20082014. The entire population was used therefore, there were no sampling. The instrument for data collection was researched design TB- proforma (TB-P). Data analysed were presented using description statistic of frequency tables and percentages while the null hypotheses were verified using chi – square statistic. The findings revealed that the highest prevalence of tuberculosis was recorded in 2009 (75.9%) and this occurred more among female. No TB cases were recorded between 2011 and 2012. Prevalence of TB was found to be more among age group 26 -35 years and lowest among age group 56 and above. Overall, a gradual rise in TB prevalence with progression of age (increase in age) was seen. The findings further show that there is a significant difference in the prevalence rate of TB based on age and there is no significant difference in the prevalence rate according to gender. The study recommended among other things that government should regularly conduct population based TB prevalence survey both in urban and rural areas of the 36 States of the federation.